2007
DOI: 10.1042/bj20061738
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes and Fas-mediated liver cell death

Abstract: A number of studies, mostly performed ex vivo, suggest that lysosomes are involved in apoptosis as a result of a release of their cathepsins into the cytosol. These enzymes could then contribute to the permeabilization of the outer mitochondrial membrane; they could also activate effector caspases. The present study aims at testing whether the membrane of liver lysosomes is disrupted during Fas-mediated cell death of hepatocytes in vivo, a process implicated in several liver pathologies. Apoptosis was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
3
11
1
Order By: Relevance
“…However, our results show that lysosome destabilization is a very late event in Fas/CD95 induced apoptosis and not an early event, as suggested by Brunk and Svensson [19], although this may depend on cells or cell line used. Despite the very late appearance of cells with destabilized lysosomes, our results do not support the idea that secondary necrosis is responsible for lysosome breakdown [39], as only 5–11% of late apoptotic/necrotic cells were observed even at the latest time point (18 h), whereas 30–35% of cells with destabilized lysosomes have been found already after 15 h (Figs. 1 and 2).…”
Section: Discussioncontrasting
confidence: 98%
“…However, our results show that lysosome destabilization is a very late event in Fas/CD95 induced apoptosis and not an early event, as suggested by Brunk and Svensson [19], although this may depend on cells or cell line used. Despite the very late appearance of cells with destabilized lysosomes, our results do not support the idea that secondary necrosis is responsible for lysosome breakdown [39], as only 5–11% of late apoptotic/necrotic cells were observed even at the latest time point (18 h), whereas 30–35% of cells with destabilized lysosomes have been found already after 15 h (Figs. 1 and 2).…”
Section: Discussioncontrasting
confidence: 98%
“…However, knocking out the cathepsins failed to completely block apoptosis but led only to its suppression (44 -47), arguing against an essential role of cathepsins in this pathway. This is also more consistent with recent data on Fas-induced apoptosis, where lysosomes were indeed observed to be broken but substantially later than mitochondria (48,49). These latter findings are more consistent with a bystander role of cathepsins, although their role in an amplification loop through mitochondria cannot be excluded.…”
Section: Differential Roles Of Lysosomal Cathepsins In Cell Deathsupporting
confidence: 81%
“…That lysosomal enzymes participate in secondary necrosis is also suggested by the observation that, in apoptosis induced in vitro in the epithelial cell line LLC-PK1 by S-(1,2-dichlorovinyl)-L-cysteine, inhibition of cathepsin B resulted in inhibition of secondary necrosis [123]. In support of this interpretation, recent results with caspase 3-associated apoptosis induced in Jurkat cells by treatment with anti-Fas showed that the terminal cell lysis due to secondary necrosis was concomitant with lysosome rupture [124].…”
Section: Apoptotic Secondary Necrosismentioning
confidence: 64%